2017
DOI: 10.1186/s12967-017-1260-2
|View full text |Cite
|
Sign up to set email alerts
|

High expression of ETS2 predicts poor prognosis in acute myeloid leukemia and may guide treatment decisions

Abstract: Background ETS2 is a downstream effector of the RAS/RAF/ERK pathway, which plays a critical role in the development of malignant tumor. However, the clinical impact of ETS2 expression in AML remains unknown. MethodsIn this study, we evaluated the prognostic significance of ETS2 expression using two relatively large cohorts of AML patients.ResultsIn the first cohort, compared to low expression of ETS2 (ETS2 low), high expression of ETS2 (ETS2 high) showed significant shorter OS, EFS and RFS in the current treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…As a result, we defined 36 significant TF regulators predicted to regulate 2,410 gene targets from the inferred B-ALL regulatory network previously described, with the number of targets for each TF shown in Supplemental Fig 4c . We note that many TFs (FOXM1 38 , ETS2 39, 40 , BCL11A 41 , FOXO1 42 , etc.) with significantly altered activity are implicated in cancer and could therefore potentially contribute to tumorigenesis in CRLF2 -High B-ALL patients.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As a result, we defined 36 significant TF regulators predicted to regulate 2,410 gene targets from the inferred B-ALL regulatory network previously described, with the number of targets for each TF shown in Supplemental Fig 4c . We note that many TFs (FOXM1 38 , ETS2 39, 40 , BCL11A 41 , FOXO1 42 , etc.) with significantly altered activity are implicated in cancer and could therefore potentially contribute to tumorigenesis in CRLF2 -High B-ALL patients.…”
Section: Resultsmentioning
confidence: 89%
“…The network-driven approach also identified a number of significant TF regulator motifs including ETS2 40 , FOXO1 42 , EGR1 82 , and FOXM1 38, 55, 56 , which are implicated in hematological malignancies. FOXM1 could be an important regulator in CRLF2 -overexpressing cells due to its crucial role in cell proliferation and its implication in various cancer types, as described earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of these pathways were closely associated with AML progression. Liu et al reported that the high level of expression of ETS2 predicted the unfavorable prognosis for AML patients (31). ENO1 functions as a glycolytic enzyme and was found to be upregulated in the AML samples (32).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, Goldberg et al studied that PIM-1 and the RAS pathway are potential therapeutic targets of high-risk leukemia [ 34 ]. In addition, ETS2, a downstream effector of the RAS/RAF/ERK pathway, the same as PIM-1, which plays a crucial role in cell growth and Fu et al also reported that high expression of ETS2 predicted poor prognosis in acute myeloid leukemia [ 35 , 36 ]. This illustrates that our finding may be relevant to these studies.…”
Section: Discussionmentioning
confidence: 99%